Mediating Effect of Job Satisfaction on Work Culture, Motivation, and Employee Performance Among Hospital Staff - Adif, Shannastaniar Aisya; Pamungkas, Mohammad Adreng; Cholifah, Siti (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Employee performance in hospitals is influenced by individual motivation and the organizational environment, yet the mechanisms linking these factors are underexplored. This study examined the effects of work culture and motivation on employee performance, with job satisfaction as a potential mediator. A cross-sectional design and Hayes’ PROCESS macro (Model 4) were used to assess direct and indirect effects. Results indicated that work motivation significantly predicted job satisfaction, which in turn predicted performance. The direct effect of motivation on performance was non-significant, indicating full mediation. Conversely, work culture had a strong direct effect on performance but did not significantly influence job satisfaction, and its indirect effect was non-significant. These findings support two explanatory mechanisms: a psychological pathway, where motivation affects performance via satisfaction, and a structural pathway, where work culture directly influences performance. These insights inform strategies for enhancing employee outcomes in hospital settings through both motivational and organizational interventions.